Budgetary Participation, Motivation, and Managerial Performance. - Brownell, Peter; McInnes, Morris (The Accounting Review, 1986)
ABSTRACT: This paper reports the results of an empirical study designed to assess the relationship of budgetary participation to motivation and performance among middle-level managers in three manufacturing firms. Expectancy theory provides the theoretical framework for specifying and estimating motivation. It is hypothesized that motivation mediates the effect of participation on performance. Participation and performance are found to be significantly positively related; however, the path between them through motivation explains very little of this, principally because participation's relationship with motivation is Insignificant. The correlations between participation and the elements in the expectancy model show a positive relationship with the expectancies, counteracted by a negative relationship with the intrinsic valences. An Interpretation of participation's potential effects on budgetary slack is offered as a possible explanation of this unexpected finding.